Pyrolysis-gas chromatography : mass spectrometry of polymeric materials - Kusch, Peter (World Scientific, 2019)
"The methodology of analytical pyrolysis-GC/MS has been known for several years, but is seldom used in research laboratories and process control in the chemical industry. This is due to the relative difficulty of interpreting the identified pyrolysis products as well as the variety of them. This book contains full identification of several classes of polymers/copolymers and biopolymers that can be very helpful to the user. In addition, the practical applications can encourage analytical chemists and engineers to use the techniques explored in this volume. The structure and the functions of various types of pyrolyzers and the results of the pyrolysis-gas chromatographic-mass spectrometric identification of synthetic polymers/copolymers and biopolymers at 700°C are described. Practical applications of these techniques are also included, detailing the analysis of microplastics, failure analysis in the automotive industry and solutions for technological problems"--
Keywords: polymery -- analýza; plynová chromatografie; pyrolýza; polymers -- analysis; gas chromatography; pyrolysis; monografie; monographs